The Effects of Social Perception on Moral Judgment - Jin, Wen Ying; Peng, Ming (Frontiers in Psychology, 2021)
When people express a moral judgment, others make inferences about their personality, such as whether they are warm or competent. People may use this interpersonal process to present themselves in a way that is socially acceptable in the current circumstances. Across four studies, we investigated this hypothesis in Chinese culture and showed that college student participants tended to associate others’ deontological moral judgments with warmth and utilitarian moral judgments with competence (Study 1, Mage = 21.1, SD = 2.45; Study 2, Mage = 20.53, SD = 1.87). In addition, participants made more deontological judgments after preparing to be interviewed for a job requiring them to be in a warm social role, and more utilitarian judgments after preparing for a job requiring them to be in a competent social role (Study 3, Mage = 19.5, SD = 1.63). This effect held true in moral dilemmas involving different degrees of hypothetical personal involvement, and appeared to be mediated by the perception of others’ expectations (Study 4, Mage = 19.92, SD = 1.97). The results suggest an important role for social cognition as an influence on moral judgments in Chinese culture.